Report for Sabbatical Leave, Spring 2011. - Piemontese, Luisa (2011)
Studied contemporary poetry in Spanish by Spanish-speaking authors living in Connecticut. Works of four poets were chosen for a bilingual anthology. Seventy five percent of poems selected for this publication were translated and their analytical study completed. In addition, audio interviews were completed, and multimedia presentation, including photos, biographies, and bilingual readings was compiled and given. Publishing companies were identified for submission of the anthology's proposal.
Keywords: Connecticut; Poets; Spanish American; United States; dept.wll; faculty_collection; sabbatical_report